The grammar of beauty through the language of advertisements on Vaseline US and Indonesia websites - Gratia, Agata Filia Dei; Andriani, Merry (Universitas Mulawarman, 2025)
This study examines how the systemic functional grammar is employed in Vaseline advertisements to construct and convey notions of beauty, as well as the underlying brand messages communicated through promotional content. Specifically, it compared the linguistic features on the Vaseline ads for the US and Indonesia. Qualitative-descriptive methodology was employed in this study. The data collected correlated to the transitivity found in the sentences on both advertisements. The Transitivity in SFG theory by Halliday & Matthiessen serves as the analytical framework, which focuses on three elements of transitivity: process, participants, and circumstance. The findings show that Vaseline advertisements' transitivity refers to a reflection of relational and material processes. Vaseline US focuses on its line of products and services to achieve dream skin, while Vaseline Indonesia emphasizes its key ingredients and reputation as an innovator. The concept of beauty in both nations is also reflected in the transitivity. Vaseline US encourages Americans to strive for healthy skin, while Vaseline Indonesia perpetuates the myth of ageless and bright skin. In conclusion, Vaseline's technique of differentiating linguistic elements in Vaseline advertisements based on the concept of beauty standards might be considered effective as it makes Vaseline becomes one of the biggest beauty brands.